PBL Impact on Learning Outcomes in Computer Engineering: A 12-Year Analysis - Pedro José Lara-Bercial; María Cruz Gaya-López; Juan-Miguel Ma; Silvia Lavado-Anguera (MDPI AG, 2024)
This article describes an evaluation of the Project-Based Learning (PBL) methodology implemented in the STEAM School of Universidad Europea in the Computer Engineering degree. The study raises research questions related to the perception of technical and soft skills acquired by students who used or considered PBL as their primary learning methodology compared to those who did not. Students' motivation and adaptability to work after graduation have also been examined. The sample of students includes graduates from the last 20 years and therefore analyzes both the period in which the methodology was already implemented (from 2012) and some previous years. The study concludes that students who have identified or experienced PBL as their main learning methodology perceive a better acquisition of technical competencies and some soft skills, as well as better motivation and adaptability to the work environment.